1993
DOI: 10.1007/bf00185891
|View full text |Cite
|
Sign up to set email alerts
|

Fetal antigen 1 (FA1) in the human pancreas: cell type expression, topological and quantitative variations during development

Abstract: Monospecific rabbit anti-human fetal antigen 1 (FA1), was used to examine the distribution of FA1 during the development of the human fetal pancreas and liver using an indirect immunoperoxidase technique. FA1 was expressed by 94% of the glandular epithelial cells of the branching ducts in the pancreatic anlage at week 7 of gestation. This pattern changed during the development of the human pancreas, 64% of the glandular cells being FA1 positive at week 17 of gestation, decreasing to 11% in the infant (4 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…We previously demonstrated that Dlk1 expression and secretion in b-cells are stimulated in vitro and in vivo by recombinant Glu-OCN, an inducer of insulin expression by b-cells (34). Considering that DLK1 is colocalized with insulin in adult b-cells (37,38) and that the secretion of DLK1 and insulin have been reported to be stimulated by the same hormones (including growth hormone and prolactin) (37,39), it is plausible that OCN uses a similar mechanism to stimulate the secretion of sDLK1 and insulin. In this context, it is important to note that OCN favors the receptor Gprc6a in insulin secretion in b-cells (31).…”
Section: Discussionmentioning
confidence: 98%
“…We previously demonstrated that Dlk1 expression and secretion in b-cells are stimulated in vitro and in vivo by recombinant Glu-OCN, an inducer of insulin expression by b-cells (34). Considering that DLK1 is colocalized with insulin in adult b-cells (37,38) and that the secretion of DLK1 and insulin have been reported to be stimulated by the same hormones (including growth hormone and prolactin) (37,39), it is plausible that OCN uses a similar mechanism to stimulate the secretion of sDLK1 and insulin. In this context, it is important to note that OCN favors the receptor Gprc6a in insulin secretion in b-cells (31).…”
Section: Discussionmentioning
confidence: 98%
“…Dlk1 is also expressed in pancreatic 尾 cells [17], leydig cells and the theca interna and Hilus cells of the ovary [18], suggesting that Dlk1 has endocrine-related functions. Previous studies investigating potential endocrine links to Dlk1 have focused primarily on its regulation by a number of hormones.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being expressed in preadipocytes, Dlk1 is also expressed in many endocrine tissues, including the growth hormone-producing somatotroph cells of the pituitary gland [16], insulinproducing 尾 cells [17], sex hormone-producing leydig cells of the testis, and the theca interna and the Hilus cells of the ovary [18]. Dlk1 expression in such a large number of endocrine cells suggests that Dlk1 has endocrine functions.…”
Section: Introductionmentioning
confidence: 99%
“…Earliest in the evolution among endocrine cells are the glucagon-immunoreactive (IR) cells, known from the incipient formation of the pancreatic buds, followed by insulin-IR (4,5), somatostatin-IR and PP-IR cells, all four cell types being present by embryonic week (ew) 8 to 9 (6).…”
Section: Introductionmentioning
confidence: 99%